The effect of peer teaching and think pair share on rhythmic gymnastics learning outcomes - Hasan, Muhammad Lutfi; Royana, Ibnu Fatkhu; Zhannisa, Utvi Hinda (CV Rezki Media, 2025)
Background: Rhythmic gymnastics plays a vital role in developing students' motor skills, coordination, and rhythm, yet many still face challenges in mastering movement concepts. Objectives: This study compared the effectiveness of Peer Teaching and Think Pair Share (TPS) cooperative learning models in improving rhythmic gymnastics learning outcomes. Methods: A quasi-experimental design with a two-group pretest–posttest was conducted on 68 eighth-grade students (male and female) at State Junior High School 4 Semarang, divided into Peer Teaching (n=34) and TPS (n=34) groups. Learning outcomes were assessed using a validated rhythmic gymnastics performance test, and data were analyzed descriptively with gain score calculation. Results: The TPS group achieved a greater improvement in posttest scores (from 67.21 to 79.59; +18.41%) compared to the Peer Teaching group (from 79.18 to 79.85; +0.85%). These results indicate that TPS enhances students' understanding, coordination, and engagement in rhythmic gymnastics learning. Conclusions: TPS is recommended for physical education teachers to improve performance, particularly for students with lower initial skills. Further studies should explore its long-term effects and retention.